2019
DOI: 10.1186/s12889-019-7961-0
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of psychological wellness for children and adolescents in rural NSW

Abstract: BackgroundThe mental wellness of children and adolescents in rural Australia is under researched and key to understanding the long-term mental health outcomes for rural communities. This analysis used data from the Australian Rural Mental Health Study (ARMHS), particularly the parent report Strengths and Difficulties Questionnaire (SDQ) measure for children under 18 years old and their reporting parent’s demographic information to compare this sample’s mental wellness scores to the Australian norms and to iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…29 Our finding that RR and RU adolescents had worse mental health symptoms than their UU peers was in line with prior studies conducted in China 31 and in other countries (eg, Korea 32 and Australia). 33 Certain behavioural and sociodemographic differences between the urbanrural subgroups explained most of the disparities, which corresponded with the results of a previous study. 34 For example, our study indicated that the significant urbanrural differences of adolescent mental health problems were mainly attributed to screen time, which previous researches have linked it to less face-to-face communication with peers and families, less outdoor physical activity and receiving plenty of potentially inappropriate information.…”
Section: Discussionsupporting
confidence: 89%
“…29 Our finding that RR and RU adolescents had worse mental health symptoms than their UU peers was in line with prior studies conducted in China 31 and in other countries (eg, Korea 32 and Australia). 33 Certain behavioural and sociodemographic differences between the urbanrural subgroups explained most of the disparities, which corresponded with the results of a previous study. 34 For example, our study indicated that the significant urbanrural differences of adolescent mental health problems were mainly attributed to screen time, which previous researches have linked it to less face-to-face communication with peers and families, less outdoor physical activity and receiving plenty of potentially inappropriate information.…”
Section: Discussionsupporting
confidence: 89%
“…In 2019 UNICEF estimated that there were 1.2 billion adolescents (aged 10–19 years), which represents approximately 16% of the global population ( UNICEF, 2020a ). It is further estimated that approximately 50% of all mental disorders have their onset during adolescence ( Patalay and Gage, 2019 ; Peters et al, 2019 ; UNICEF, 2020b ). According to the World Health Organization (WHO) ( World Health Organization, 2020 ), one in seven adolescents experienced a mental health condition in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO) ( World Health Organization, 2020 ), one in seven adolescents experienced a mental health condition in 2019. Poor mental health hinders healthy adolescent development and is associated with poorer health, social and economic outcomes across their lifetime ( Patalay and Gage, 2019 ; Peters et al, 2019 ). Adolescent mental disorders represent a significant burden of disease on health systems, particularly in low- and middle-income countries (LMICs), where mental health services and resources are lacking ( Peters et al, 2019 ; World Health Organization, 2020 ; Sorsdahl et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Use of broader scale score is preferred over the sub-scale scores in community samples with low-risk of mental health difficulties [ 20 ]. Therefore, the total difficulties score was used to measure the psychological well-being of adolescents in this study as done by similar studies in the past [ 14 , 21 ]. Higher total difficulties score indicates poorer psychological well-being.…”
Section: Methodsmentioning
confidence: 99%